Diospyros mespilifoemis hochst Modulates the Hippocampus and Prefrontal Cortex of Wistar Rat following Lithium chloride pilocarpine-induced Epilepsy - Sunday Yinka Olatunji; Oluwafemi Ezekiel Kale; Oluseyi Abimbola Ogunsola; John Afees Olanrewaju; Ijeoma Esiaba; Taiye Adelodun; Olubunmi Philip Ogunnaike (Babcock University Medical Journal)
Objectives: Epilepsy is a disease with vast complexity and diverse clinical manifestations causing neuronal misfiring. Diospyros mespiliformis (DM) possesses anti-epileptic properties.